Report of the Task Force for the Study of Eco-Development in the Himalayan Region - Planning Commission (Planning Commission, 1982)
There are large variations in topography, climate and soil conditions in the Himalaya representing areas from tropical valleys and hills to arctic mountains. As seen from the land use pattern given at Annexure II about 53.2 per cent of the reporting area is Classified as forest land though there are large variations from minimum of 8.3% in Meghalaya to a maximum of 91.3 per cent in Arunachal Pradesh. Besides the land under forest, about 28.2 per cent of other land is classified as pasture land. The net area sown is hardly 9.7 per cent of the total reporting area in the region.
Planning Commission
Planning Commission